Clostridium butyricum isolated from giant panda can attenuate dextran sodium sulfate-induced colitis in mice - Yu, Shuran; Xie, Junjin; Guo, Qiang; Yan, Xia; Wang, Yuxiang; Leng, Tangjian; Li, Lin; Zhou, Jielong; Zhang, Wenping; Su, Xiaoyan (Frontiers in Microbiology, 2024)
Objective: Probiotics are beneficial to the intestinal barrier, but few studies have investigated probiotics from giant pandas. This study aims to explore the preventive effects of giant panda-derived Clostridium butyricum on dextran sodium sulfate (DSS)-induced colitis in mice. Methods: C. butyricum was administered to mice 14 days before administering DSS treatment to induce enteritis. Results: C. butyricum B14 could more effectively prevent colitis in mice than C. butyricum B13. C. butyricum B14 protected the mouse colon by decreasing the histology index and serum interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-α) levels, which improved intestinal inflammation-related symptoms. In addition, the treatment led to the regulation of the expression of Tifa, Igkv12-89, and Nr1d1, which in turn inhibited immune pathways. The expression of Muc4, Lama3, Cldn4, Cldn3, Ocln, Zo1, Zo2, and Snai is related the intestinal mucosal barrier. 16S sequencing shows that the C. butyricum B14 significantly increased the abundance of certain intestinal probiotics. Overall, C. butyricum B14 exerted a preventive effect on colitis in mice by inhibiting immune responses, enhancing the intestinal barrier and increasing the abundance of probiotic species. Thus, C. butyricum B14 administration helps regulate the balance of the intestinal microecology. It can suppress immune pathways and enhance barrier-protective proteins.